Research and development of genetically engineered soybean using insect-resistance genes derived from Bacillus thuringiensis - Thu Hien, Le Thi; Bich Hang, Pham Le; Tuong Van, Nguyen; Minh Thanh, Le Thi; Thi Hang, Dao; Hai Ha, Nguyen; Hong Hanh, Ha; Thu Hue, Huynh Thi; Nhat Linh, Nguyen; Thanh Hoa, Nguyen Thi; et al. (Vietnam Journal of Biotechnology, 2020)
Soybean (Glycine max) is one of the crops which have high economic value and serve for food, feed and process of many countries around the world. However, there are many factors affecting the productivity of soybean, of which insect pests and diseases are the most harmful agents. Therefore, an application of biotechnology to transfer insect resistance genes derived from a species of bacteria Bacillus thuringiensis can contribute to increase soybean yield and significantly reducing pesticide use. Currently, there are many insecticidal proteins detected from B. thuringiensis such as Cry, Cyt and Vip with a broad and specific spectrum belonged to several orders Lepidoptera, Diptera, Coleoptera, Homopera, and Nematoda. Numerous studies have been implemented over the world to transfer genes encoding these proteins in combination or modified forms to increase their toxicity. Several events of genetically engineered soybean with stacked traits of insect resistance and herbicide tolerance are commercialized and approved to be cultured in many countries such as MON 87701 × MON 89788 or DAS-81419-2. In Vietnam, studies on genetically engineered soybean with insect resistance trait has been carried out. Moreover, the exploitation, screening and selection of high biodiversity and indigenous B. thuringiensis strains which habors specific genes capable of killing targeted insects and serve as materials for plant transformation are great scientific meaning and potential practical application. This will be an important source of materials to create many soybean cultivars with good ability of insect resistance in order to meet specific needs.